ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PT. GARUDA INDONESIA (PERSERO), TBK PERIODE 2014-2024 - Ruli Awaldi Juliana; Ananda Hadistia (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study explores the financial performance of PT Garuda Indonesia Persero Tbk from 2014 to 2024, focusing on the analysis of liquidity and profitability ratios. The objective of this research is to understand how well the company is able to meet short-term obligations and how efficiently it generates profit. Using a descriptive quantitative analysis method, data were collected from the company's annual financial statements. The results indicate that liquidity ratios, such as the average Current Ratio of 64.21 percent, average Quick Ratio of 56.02 percent, and average Cash Ratio of 33.21 percent, reflect serious challenges in meeting short-term obligations. Meanwhile, profitability ratios, including Return on Assets (ROA) with an average of -131.77 percent, Return on Equity (ROE) averaging -69 percent, and Net Profit Margin (NPM) averaging -35.48 percent, also highlight the urgent need for improvement. Although there is hope with a positive net profit recorded in 2022, challenges to achieving financial sustainability remain. Therefore, the results of this study are expected to provide valuable insights for management and stakeholders in formulating steps for improvement in the future, in line with the industry standards set by Kasmir in 2017.